1977
DOI: 10.1007/bf00498689
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic receptor systems on the noradrenergic neurones of the rabbit pulmonary artery

Abstract: A search was performed for presynaptic, release-modulating receptor systems on the post-ganglionic sympathetic nerves of rabbit pulmonary artery. Strips of the artery were preincubated with (-)-3H-noradrenaline and then superfused and stimulated transmurally. 1. Tetrodotoxin, guanethidine, and omission of calcium all suppressed the stimulation-evoked overflow of tritium, thus confirming selective release from noradrenergic neurones. 49% of the stimulation-evoked overflow of total consisted of 3H-noradrenaline,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
67
1
1

Year Published

1978
1978
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(79 citation statements)
references
References 36 publications
10
67
1
1
Order By: Relevance
“…At very low or near maximal endogenous synthesis rates of cyclic AMP, phosphodiesterase inhibition may have little effect. Starke et al (1975) and Endo et al (1977) extensively studied 0-adrenoceptor enhancement of noradrenaline release in the rabbit pulmonary artery at various frequencies of electrical stimulation and concluded that prejunctional P-adrenoceptors were not functional in this tissue. In the present study, in rabbit pulmonary artery incubated with [3H]-noradrenaline and stimulated at 1 Hz, isoprenaline alone also failed to enhance the S-I outflow of radioactivity.…”
Section: Discussionmentioning
confidence: 99%
“…At very low or near maximal endogenous synthesis rates of cyclic AMP, phosphodiesterase inhibition may have little effect. Starke et al (1975) and Endo et al (1977) extensively studied 0-adrenoceptor enhancement of noradrenaline release in the rabbit pulmonary artery at various frequencies of electrical stimulation and concluded that prejunctional P-adrenoceptors were not functional in this tissue. In the present study, in rabbit pulmonary artery incubated with [3H]-noradrenaline and stimulated at 1 Hz, isoprenaline alone also failed to enhance the S-I outflow of radioactivity.…”
Section: Discussionmentioning
confidence: 99%
“…increase in overflow must be due to an increase in transmitter liberation by the nerves. The simplest explanation for this is an inhibition of the presynaptic inhibitory a-adrenoceptors on the noradrenergic nerves (see Endo, Starke, Bangerter & Taube, 1977). The net effect upon the response of the inhibition of pre-and postsynaptic a-adrenoceptors will be determined by the relative potency of the antagonist at the two receptor sites.…”
Section: Discussionmentioning
confidence: 99%
“…A 2F Fogarty arterial embolectomy catheter (Baxter Health Care Co, Santa Ana, Calif) was inserted into the artery and advanced proximally into the iliac artery past the bifurcation into the aorta. The 16 OOOg in a microfuge for 5 minutes.…”
Section: Methods Animalsmentioning
confidence: 99%